NATURE AND SELF IN WORDSWORTH’S TINTERN ABBEY (International Journal of Food and Nutritional Sciences, 2022)
In Tintern Abbey, William Wordsworth explores the deep relationship between nature and the self, reflecting on the role nature plays in shaping personal identity, emotional well-being, and spiritual growth. The poem is a meditation on the power of nature to provide renewal, solace, and wisdom, emphasizing how nature influences the speaker’s perception of life and his evolving self-awareness over time. Wordsworth’s speaker returns to the Wye Valley after five years, and through his observations of the landscape, he reflects on the transformation in his relationship with nature from youthful joy to a more mature, introspective connection. The poem reveals that nature acts as a source of spiritual renewal, offering comfort and clarity to the speaker during times of emotional turmoil. Through the lens of memory, the speaker recalls the profound influence nature had on him in his youth, demonstrating how nature’s impact endures even in its absence. This memory serves as a guide for the present, indicating the continuity between past and present experiences and their combined role in the development of the self.